THE IMPACT OF EMPLOYEE TRAINING AND DEVELOPMENT ON ORGANIZATIONAL EFFECTIVENESS - Kasmin Kasmin; Rohani Lestari Napitupulu; Nofriza Efendi; Samudra Syarif Wahyu Hidayatullah (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
In an increasingly competitive business environment, employee training and development play a crucial role in enhancing organizational effectiveness. Investing in training programs helps improve employees' knowledge, skills, and abilities, leading to better performance, productivity, and overall organizational success. This study aims to explore the impact of employee training and development on organizational effectiveness using a qualitative research approach through a case study. Data were collected through semi-structured interviews with HR managers, trainers, and employees, as well as document analysis of policies and training materials. Additionally, observations were conducted to evaluate the implementation of training programs in the workplace. This paper explores the impact of employee training and development on organizational effectiveness by examining its role in enhancing employee performance, fostering innovation, and improving overall business outcomes. The discussion will also highlight best practices for designing and implementing successful training programs, as well as the challenges organizations face in achieving training effectiveness. By understanding the importance of continuous learning and skill development, organizations can create a workforce that is agile, engaged, and equipped to navigate the complexities of the modern business landscape.